Vivir la transparencia: Las casas de cristal: apogeo y decadencia de una utopía - Barbisan, Léa (Sens public, 2019)
At the beginning of the 20th century, the idea of the glass house fascinated many artists and writers of the European avant-garde. Against the background of urban densification, the ideal of a house with transparent walls questioned the value of intimacy and the attachement to the feeling of homeliness. The dream of an open space where the borders between the inside and the outside, locality and universality, the private and the public sphere would vanish, pervades the writings of Paul Scheerbart, André Breton and Walter Benjamin. First an aesthetic utopia, then a political utopia, the dream of the glass house eventually transformed into the nightmare of totalitarian surveillance. This article highlights the fantasies that crystallised around this unsettling utopia and explains the reasons for its decline.